Variation in Material Culture: Adoption of Greek Ceramics in an Indigenous Sicilian Site (8th century BCE) - Raudino, Anna (Ex Novo: Journal of Archaeology, 2018)
The archaeological study of social boundaries through the examination of the material culture reflects the intent to better understand the interaction established between two different cultures. This paper, as part of my PhD study, identifies and analyses evidence for cultural transformation in southeastern Sicily when indigenous populations came into contact with ancient Greek settlers between the end of the eighth and the beginning of the seventh centuries BCE. In particular, this current study examines indigenous pottery production and distribution, focussing on material from Monte Finocchito in southeastern Sicily and combining archaeological and anthropological approaches with the first archaeometric analyses ever carried out on this artefact assemblage. The study argues on the basis of analysis of pottery fabrics and techniques, as well as shapes and decoration, that indigenous populations maintained robust independent cultures in the early phase of their interaction with the Greeks.